Pantropical geography of lightning‐caused disturbance and its implications for tropical forests. (8th July 2020) - Gora, Evan M.; Burchfield, Jeffrey C.; Muller‐Landau, Helene C.; Bitzer, Phillip M.; Yanoviak, Stephen P.
Abstract: Lightning is a major agent of disturbance, but its ecological effects in the tropics are unquantified. Here we used ground and satellite sensors to quantify the geography of lightning strikes in terrestrial tropical ecosystems, and to evaluate whether spatial variation in lightning frequency is associated with variation in tropical forest structure and dynamics. Between 2013 and 2018, tropical terrestrial ecosystems received an average of 100.4 million lightning strikes per year, and the frequency of strikes was spatially autocorrelated at local‐to‐continental scales. Lightning strikes were more frequent in forests, savannas, and urban areas than in grasslands, shrublands, and croplands. Higher lightning frequency was positively associated with woody biomass turnover and negatively associated with aboveground biomass and the density of large trees (trees/ha) in forests across Africa, Asia, and the Americas. Extrapolating from the only tropical forest study that comprehensively assessed tree damage and mortality from lightning strikes, we estimate that lightning directly damages c. 832 million trees in tropical forests annually, of which c. 194 million die. The similarly high lightning frequency in tropical savannas suggests that lightning also influences savanna tree mortality rates and ecosystem processes. These patterns indicate that lightning‐caused disturbance plays a major and largely unappreciated role in pantropical ecosystem dynamics and global carbon cycling. Abstract : We used data from ground and satellite sensors to associate variation in lightning strike frequency with land cover types pantropically. Lightning strikes were most frequent in tropical forests and savannas, and higher lightning strike rates are associated with forest biomass, forest structure, and disturbance rates. These findings suggest that lightning plays a critical yet largely unstudied role in regulating tropical forest dynamics.